Deep-Water Caprellids (Amphipoda: Caprellidea) from the Bay of Biscay: A New Species and a New Locality Record - Laubitz, D. R.; Sorbe, J. C. (Journal of Crustacean Biology, 1996)
Two species of caprellids collected in deep-water samples from the southern Bay of Biscay are reported herein. One, Parvipalpus major, has not previously been recorded outside the Mediterranean. The second is a new species in the genus Protoaeginella. Sampling methods and ecological data are given for each species.